Community Participation and Fisheries Management in Western Uganda Case Study of Rwenshama Landing Site on Lake Edward. - Tumwesigye, Paul (Kabale University, 2025)
The study examined the effect of community participation on fisheries management at Rwenshama landing site on Lake Edward, Western Uganda. The specific objectives were: to assess the level of community participation and fisheries management; to evaluate the contribution of community participation to the formulation and enforcement of fisheries bylaws; and to determine the extent of community involvement in the arbitration of fisheries conflicts. The study adopted a descriptive case study research design, incorporating both qualitative and quantitative methods. The population comprised 2,306 individuals, and the computed sample size was 370, including members of the Landing Site Management Board, staff, and site users. Data were collected using questionnaires and interview guides. Quantitative data were analyzed using SPSS version 16. The results showed a moderate positive correlation between community participation and fisheries management, with r = 0.464, p < 0.001. Regression analysis revealed that community participation explained 21.5% of the variance in fisheries management (R² = 0.215), with an adjusted R² of 0.173. Each unit increase in community participation improved fisheries management by 0.278 units, as indicated by a standardized Beta coefficient of 0.278, with a significance level of 0.003. The findings indicate a high level of community involvement in fisheries management, particularly in decision-making and the enforcement of sustainable practices. The community has contributed significantly to the creation and enforcement of fisheries bylaws, which have been instrumental in preserving fish stocks. However, the study identified the need for greater inclusion of women in decision-making processes. Community involvement in conflict resolution is also well established, with effective mechanisms in place to address disputes. The study recommends that the Rwenshama Landing Site Management Board enhance efforts to involve women in fisheries management by collaborating with local women's groups to ensure their active participation and representation.